Role Of Habitual Risk Factors On Oral Squamous Cell Carcinoma (Update Dental College Journal, 2018)
Squamous cell carcinoma is the most common oral malignancy. Betel quid, betel quid with tobacco, smoking, alcohol consumption, mechanical irritation, genetic are the most important risk factors for Oral Squamous Cell Carcinoma (OSCC). The aim of the study was to determine the role of habitual risk factors inOral Squamous Cell Carcinoma.  Materials and Methods: This is a cross-sectional study for the determination of the risk factors of OSCC over 2 years period of January 2011 to December 2012. Department of Oral & Maxillofacial Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka, Department of Oral & Maxillofacial Surgery, Dhaka Dental College Hospital, Dhaka,National Institute of Cancer Research & Hospital (NICRH), Mohakhali, Dhaka and Health and Hope Hospital, Dhaka from January 2011 to December 2012  Results:250 patients, comprising 44% male and 56% female were included in the study. Overall mean age was 55.94±10.93 years. The patients of OSCChavemost common habit of betel quid with tobacco 124(49.6%), then betel quid with tobacco and smoking 49(19.6%), betel quid with tobacco and Gul 19(7.6%), only smoking 13(5.2%), Betel quid without tobacco and smoking 13(5.2%), betel quid without tobacco 12(5.2%), betel quid with tobacco and catechu (Khoir) 4(1.6%), betel quid with tobac- co, smoking and gul 3(1.2%), betel quid without tobacco,smoking and alcohol 2(0.8%), betel quid without tobacco and gul 2(0.8%), betel quid without tobacco, smoking and gul 1(0.4%), betel nut chewing 1(0.4%), mechanical irritation but no habit 5(2.0%) and no habitual history 2(0.8%).  Conclusion: According to this study betel quid, betel quid with tobacco, gul, smoking are the important risk factors in OSCC.Update Dent. Coll. j: 2018; 8 (1): 29-35